A study of labour laws in protecting vulnerable workers in Malaysia / Nurwahida Syamimi Ismail, Hanna Ameera Mohd Rosni and Muhammad Imran-Ul Husain Mohmad. - Ismail, Nurwahida Syamimi; Mohd Rosni, Hanna Ameera; Ismail, Nurwahida Syamimi (2013)
This study is specifically concerned with the effectiveness of labour law in protecting vulnerable workers in Malaysia. The objective of this study is to identify the existing labour law and regulations which protect, vulnerable group of workers and the effectiveness of the implementation of the existing law. The researchers observe the effectiveness of the law through the review of the relevant labour laws and interviewed different categories of respondents on vulnerable workers. In this research paper, the focus is on the three groups by vulnerable workers, namely migrant workers, women workers and children and young persons' workers. The method used by the researchers is qualitative method of research by conducting semi-structured interviews with several respondents, library and internet research. The questions conducted are on the applications of the provisions and their effects on the vulnerable group of workers. The researchers found that there are laws and provisions governing the vulnerable workers in Malaysia but the laws needed to be reviewed in order to ensure the rights of the vulnerable workers are protected. The researchers recommend amendments to the relevant sections of the relevant statutes to provide better protection to the vulnerable workers; creation of awareness among the vulnerable workers to avoid them being ignorant as to their rights and protections and drafting of policies to prevent the vulnerable workers from being abused and discriminated.